2002
DOI: 10.1016/s0042-6989(01)00231-0
|View full text |Cite
|
Sign up to set email alerts
|

Rpr- and hid-driven cell death in Drosophila photoreceptors

Abstract: The reaper (rpr) and head involution defective (hid) genes mediate programmed cell death (PCD) during Drosophila development. We show that expression of either rpr or hid under control of a rhodopsin promoter induces rapid cell death of adult photoreceptor cells. Ultrastructural analysis revealed that the dying photoreceptor cells share morphological features with other cells undergoing PCD. The anti-apoptotic baculoviral P35 protein acts downstream of hid activity to suppress the photoreceptor cell death driv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 42 publications
4
7
0
Order By: Relevance
“…We verified that the diap1 and DroncDN transgenes were active by showing they partially protect from GMRhid-driven cell death using the rescue of the small eye phenotype as described previously (Hay et al, 1995;Hawkins et al, 2000). However, unlike P35 (Hsu et al, 2002), they were not effective in the rescue of ninaEhid (data not shown).…”
Section: Methodssupporting
confidence: 75%
See 3 more Smart Citations
“…We verified that the diap1 and DroncDN transgenes were active by showing they partially protect from GMRhid-driven cell death using the rescue of the small eye phenotype as described previously (Hay et al, 1995;Hawkins et al, 2000). However, unlike P35 (Hsu et al, 2002), they were not effective in the rescue of ninaEhid (data not shown).…”
Section: Methodssupporting
confidence: 75%
“…Figure 3A shows data collected from observation of the DPP structure in this experiment. We confirmed that GMRp35 was capable of suppressing photoreceptor degeneration triggered by hid expression under control of the ninaE rhodopsin promoter (Hsu et al, 2002). In contrast, the DPP was retained for only ϳ1 d longer in norpA with P35 than seen in norpA flies lacking P35.…”
Section: Limited P35 Suppression Of Norpa Degenerationsupporting
confidence: 72%
See 2 more Smart Citations
“…No retinular or ocellar fibers were observed in adult GMR-hid homozygotes with an anti-chaoptin antibody or in adult GMR-hid heterozygotes with a Rh6-gfp reporter gene (data not shown). The complete disappearance of all photoreceptor cell bodies expressing hid from Rh1 promoter sequences has been similarly reported recently (Hsu et al, 2002). w norpA p24 (Pearn et al, 1996) (Renn et al, 1999), yw; tim-gal4 (Kaneko, 1998), and yw; UAS-cry (Emery et al, 2000b) flies have been described previously.…”
Section: Methodssupporting
confidence: 72%